2010
DOI: 10.1111/j.1440-1681.2009.05323.x
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin compromises myocardial contractile function and mitochondrial ultrastructure: Role of endoplasmic reticulum stress

Abstract: 1. Cisplatin is a potent chemotherapeutic agent with broad-spectrum antineoplastic activity against various types of tumours. However, a major factor limiting treatment with cisplatin is its acute and cumulative cardiotoxicity. The aim of the present study was to explore the effect of cisplatin on myocardial contractile function and the possible underlying cellular mechanisms. 2. C57 mice were treated with cisplatin (10 mg/kg per day, i.v.) or vehicle (0.9% NaCl) for 1 week and myocardial function was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 37 publications
6
64
0
2
Order By: Relevance
“…Dolci et al 20 have classified the chemotherapy induced cardiotoxicity in two patterns: (1) Acute or subacute cardiotoxicity and (2) CP-induced cardiotoxicity is related to excessive oxidative stress and apoptosis 25 . Ma et al 6 have reported that depressed cardiomyocyte contraction and mitochondrial abnormalities, increased endoplasmic reticulum stress and associated apoptosis caused cardiac damage following CP treatment. Cardiomyocytes containing numerous mitochondria constitute an important site for CP accumulation and this condition eventually can lead to mitochondrial DNA damage 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dolci et al 20 have classified the chemotherapy induced cardiotoxicity in two patterns: (1) Acute or subacute cardiotoxicity and (2) CP-induced cardiotoxicity is related to excessive oxidative stress and apoptosis 25 . Ma et al 6 have reported that depressed cardiomyocyte contraction and mitochondrial abnormalities, increased endoplasmic reticulum stress and associated apoptosis caused cardiac damage following CP treatment. Cardiomyocytes containing numerous mitochondria constitute an important site for CP accumulation and this condition eventually can lead to mitochondrial DNA damage 26 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several experimental and clinical studies support the idea that the enhancement of oxidative stress may involve in this insult 6 .…”
Section: Introductionmentioning
confidence: 94%
“…The cisplatinrelated cardiac dysfunction is due to the disruption of the mitochondrial membrane as well as the ultrastructural abnormalities seen in mitochondria. It was shown that, following CIS treatment, the endoplasmic reticulum stress response and apoptosis were increased in cardiomyocytes (15). CIS was shown to lead to renal injury by triggering the formation of mitochondrial reactive oxygen species in renal tubular cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…The sinus node may be influenced by several stimuli, and a hyperstimulation of the parasympathic as well as of the sympathic system may cause abnormal function of the sinus node and abnormal intraatrial or atrioventricular conduction. Cisplatin is cardiotoxic and may lead to left ventricular dysfunction and depressed cardiomyocyte contraction associated with mitochondrial abnormalities, enhanced endoplasmic reticulum stress and apoptosis [1,2].…”
Section: Discussionmentioning
confidence: 99%